Recent developments in biosensors for healthcare and biomedical applications: A review. (1st January 2021) - Mohankumar, P.; Ajayan, J.; Mohanraj, T.; Yasodharan, R.
Abstract: The development of biosensors is gaining tremendous attention in the fields of biomedicine and healthcare due to their wide use in clinical care, medicine and food processing. Biosensors have been used for the detection of diseases, diagnosis, treatment, patient health monitoring and human health management. Biosensors have been emerged as the future of cardiac healthcare. Biosensors can also be used for the recognition of microorganisms like bacteria, fungi and viruses. In this review article, recent developments in biosensors such as bioresorbable biosensors, flexible and wearable biosensors, electrochemical biosensors, enzymatic biosensors, FET biosensors, metal oxide biosensors, micro fluidic biosensors, plasmonic biosensors and polymer organic biosensors for healthcare and biomedical applications is intensively studied. This article also highlights the recent advances being made in the development of materials for the fabrication of biosensors.